Student Participation in Conducting Environmental Impact Analysis Using Artificial Intelligence: A Conceptual Review - Felly Ferol Warouw; Jeffrey Andre Delarue; Sonny Dj. Mailangkay; Treesje Katrina Londa; Lady Grace Jane Giroth (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2025)
about major changes in the fields of education and architectural practice. This article aims to conceptually examine student participation in conducting environmental impact assessments (EIA) through the use of AI technology in the Architecture Study Program at Manado State University. A literature review was conducted on various recent studies and publications discussing the integration of AI in architectural education, environmental sustainability, and digital-based environmental analysis systems. The study employs a systematic literature review (SLR) approach, filtering academic databases from 2019 to 2025 to synthesize current pedagogical frameworks. The results of the study show that AI technology can increase student engagement in project-based environmental learning, accelerate EIA data processing, and facilitate digital simulation-based decision making. AI also has the potential to strengthen environmental education through reflective, collaborative, and interactive approaches. However, challenges remain, such as digital literacy, infrastructure readiness, and the need for curriculum adaptation. This article concludes that student participation can be significantly increased through the application of AI that is pedagogically and contextually designed in the architecture curriculum.